2014
DOI: 10.3141/2433-06
|View full text |Cite
|
Sign up to set email alerts
|

Generating Hourly Climatic Data for Pavement Design from Available Weather Information

Abstract: This study addressed the need for more detailed weather information in the context of pavement design with the Mechanistic–Empirical Pavement Design Guide from weather information available for Chile. An initial database was developed with the available hourly data in the country, and the sensitivity of distress predictions for Chilean weather was studied. Because of the limited availability of hourly climatic data, different methods were proposed for completing the missing data. As their inputs, the developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For the unbound layers and subgrade soils, the program uses a monthly or semi-monthly temperature (if the pavement is exposed to freeze and thaw cycles) to compute the modulus. In addition, a recently published study concluded that the MEPDG predicted performance was not significantly affected when average daily climatic data was used instead of actual hourly climatic data [15].…”
Section: Climatic Data Collection and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…For the unbound layers and subgrade soils, the program uses a monthly or semi-monthly temperature (if the pavement is exposed to freeze and thaw cycles) to compute the modulus. In addition, a recently published study concluded that the MEPDG predicted performance was not significantly affected when average daily climatic data was used instead of actual hourly climatic data [15].…”
Section: Climatic Data Collection and Processingmentioning
confidence: 99%
“…Delgadillo et al developed an initial climatic database comprising of 17 weather stations across Chili [15]. They also studied the sensitivity of the distress predictions for the Chilean weathers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation